The Persistent Effects of Short-Term Peer Groups in Higher Education - Petra Thiemann (Lund University, School of Economics and Management, Department of Economics, 2018)
This paper studies the persistent effects of short-term peer exposure in a college setting. I exploit the random assignment of undergraduates to peer groups during a mandatory orientation week and follow the students until graduation. High levels of peer ability in a group harm the students' test scores and lead to increases in the probability of early dropout; this result is driven by the adverse effect of high-ability peers on low-ability students. I find suggestive evidence for discouragement effects: Peer ability is negatively correlated with the students' confidence in their academic ability after the first week.
Keywords: I21; I23; J24; 330; peer effect; higher education; natural experiment; ability; educational attainment; dropout; major choice